Arts in Early American History. : Needs and Opportunities for Study - Whitehill, Walter Muir (Published for the Omohundro Institute of Early American History and Culture, Williamsburg, Virginia, 2012)
This summary essay and the heavily annotated bibliography covering the period from the first colonization to 1826 are primarily intended to aid the scholar and student by suggesting areas of further study and ways of expanding the conventional interpretations of early American history. Originally published in 1935. A UNC Press Enduring Edition -- UNC Press Enduring Editions use the latest in digital technology to make available again books from our distinguished backlist that were previously out of print. These editions are published unaltered from the original, and are presented in affordable paperback formats, bringing readers both historical and cultural value.